Behavior modification principles and procedures - Miltenberger, Raymond G. (Cengage, 2024)
"Gain an understanding of human behavior, the factors that influence behavior and the strategies to change behavior with Miltenberger's BEHAVIOR MODIFICATION: PRINCIPLES AND PROCEDURES, 7E. This precise, step-by-step, scientific approach introduces the underlying principles and then the procedures behind behavior modification. Numerous current examples from research, clinical practice and everyday life clearly illustrate key principles. This edition offers new content that explores topics such as verbal behavior and stimulus equivalence. Updated references highlight the latest research and developments from the field, while this edition's new learning objectives direct your attention to key material. You can also use new self-assessment exercises, application and misapplication exercises, practice tests and three practice quizzes at the end of every chapter to ensure your comprehension"--Amazon's description.